Improving Reading Comprehension Through Herringbone Technique to The Eleventh Grade Students of SMA LTI-IGM Palembang - Samuri, Reno (Jurnal Ilmiah Bina Bahasa, 2018)
IMPROVING READING COMPREHENSION THROUGH HERRINGBONE TECHNIQUE TO THE ELEVENTH GRADE STUDENTS OF SMA LTI-IGM PALEMBANG   Reno, M.Pd The lecturer of Bina Darma University Jalan Jenderal Ahmad Yani No.3 Palembang Sammuri92@gmail.com     Abstract: The Research is an attempt to improve the eleventh class students? skills in reading comprehension through herringbone technique at SMA LTI-IGM. This study used pre-test and post-test of experimental and control group. The writer used a written test to collect the data, the writer gave 45 minutes with 40 questions to 40 students in the pre-test and post-test, the class is taken two; experimental class and control class, the result of pre-test and post-test was analyzed by using t-test formula to find out whether there is any significant difference between those two groups. The F test formula showed there was significant difference between students? average score in the experimental group post-test and students? average score in the control group post-test.         Abstrak : Penelitian ini dilakukan untuk meningkatkan kemampuan pemahaman bacaan di SMA LTI-IGM. Penelitian ini mengunakan pre-tes dan post-tes pada group experiment dan control. Penulis mengunakan tes tertulis dalam pengumpulan data dengan 40 pertanyaan di 45 menit. Data penelitian di analisa menggunakan t-test formula untuk mendapatkan perbedaaan yang signifikan terhadap dua group. Hasil dari formula F tes menunjukan bahwa terdapat perbedaan yang signifikan terhadap rata-rata nilai siswa pada grup experimen dan grup kontrol.